Doped Organic Micro-Thermoelectric Coolers with Rapid Response Time - Wang, Shu-Jen; Wohlrab, Steve; Reith, Heiko; Berger, Dietmar; Kleemann, Hans; Nielsch, Kornelius; Leo, Karl (Advanced Electronic Materials, 2022)
Local thermal management has important implications regarding comfort, energy consumption, and electronic device performance/lifetime. While organic thermoelectrics have emerged as promising materials for flexible thermoelectric energy harvesting devices, their potential as Peltier cooling element has been largely overlooked. Here, micro-thermoelectric coolers based on doped small molecule thin-films with a fast response time (around 25 µs) which is among the fastest micro-thermoelectric coolers reported are presented. This experimental cooling performance is supported by simulation using the finite-element method for thermal transport. The results show that organic thermoelectrics offer great potential for flexible and wearable micro-thermoelectric cooling applications.
CRIS-Team Scopus Importer:2023-03-20
Keywords: molecular doping; organic semiconductors; organic thermoelectrics; Peltier effect; thermal management